Integrated Phenotypic and Genotypic Drug Susceptibility Profiling of Mycobacterium tuberculosis Reveals High Burden of Multidrug Resistance in Northwest Nigeria - Abiola Olajumoke Tubi; Silas D. Gyar; Yakubu Boyi Ngwai; Jibril Egwu Owuna; Alice Njolke Mafe (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Tuberculosis (TB) drug resistance remains a major public health challenge in Northwest Nigeria, undermining effective disease control and treatment outcomes. This study aimed to assess the genotypic and phenotypic drug susceptibility patterns of Mycobacterium tuberculosis isolates from patients attending TB Reference Centres, with particular focus on first-line, second-line, repurposed, and new anti-TB drugs. A cross-sectional design was employed involving 503 presumptive TB cases. MTB detection and rifampicin resistance were screened using Xpert MTB/RIF Ultra, genotypic resistance was assessed using Line Probe Assay, and phenotypic susceptibility was evaluated through Lowenstein–Jensen culture and MGIT Bactec 960. Associations between conventional drugs, repurposed drugs (levofloxacin, moxifloxacin, and linezolid), and the new drug bedaquiline with multidrug-resistant TB were analyzed using chi-square tests. The results confirmed MTB in 122 patients (24.3%), including 34 rifampicin-resistant cases (28.0%). Genotypic testing showed that 11 isolates (9.0%) were resistant to at least one drug, whereas 111 isolates (90.9%) were pan-susceptible. The prevalence of multidrug-resistant TB was 17.9%, with high susceptibility to levofloxacin (95.9%) and moxifloxacin (97.5%). Chi-square analysis demonstrated statistically significant associations between conventional, repurposed, and new anti-TB drugs and multidrug-resistant TB (p < .001). Discordance between phenotypic and genotypic drug susceptibility testing was also observed. Geographically, TB hotspots were identified in Sokoto, Kaduna, and Kano, while HIV co-infection remained low (4.4%). These findings indicate that a substantial proportion of TB patients harbor drug-resistant Mycobacterium tuberculosis strains, highlighting the need for routine drug susceptibility testing, continuous monitoring of new and repurposed drug effectiveness, strengthened regional surveillance, and evidence-based TB control policies to improve treatment decisions and curb the spread of multidrug-resistant TB.